2012
DOI: 10.4028/www.scientific.net/amr.506.230
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Glutinous Rice Starch Nanofibers by Electrospinning

Abstract: Glutinous rice starch (GRS) is produced from glutinous rice which is commonly cultivated in the Northeast of Thailand. GRS contains two types of glucose polymers which are amylose and amylopectin. Glutinous rice starch nanofibers (GNF) can be produced by an electrospinning technique. This is not a complicated method but needs a high voltage power supply. The aim of this study was to understand the production of GNF and physical-chemical properties of GNF. The morphology of GNF was examined by scanning electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The thermal properties of the URB, PRB, and BS samples were determined according to the methods previously described by Jaiturong et al. [ 28 ], using a differential scanning calorimeter (DSC8000, Perkin Elmer, Billerica, MA, USA). Approximately, 2.0 mg of samples were accurately weighed in an aluminum pan with 6 μl of distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…The thermal properties of the URB, PRB, and BS samples were determined according to the methods previously described by Jaiturong et al. [ 28 ], using a differential scanning calorimeter (DSC8000, Perkin Elmer, Billerica, MA, USA). Approximately, 2.0 mg of samples were accurately weighed in an aluminum pan with 6 μl of distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…successfully fabricated native high amylose starch via a modified electrospinning setup. Also, Jaiturong et al . presented the fabrication of pure waxy rice starch nanofibers via electrospinning method and further revealed that the chemical structures of the material were not changed by this method.…”
Section: Green and Biodegradable Polymer Materialsmentioning
confidence: 99%
“…[24] Kong et al [25] successfully fabricated native high amylose starch via a modified electrospinning setup. Also, Jaiturong et al [26] presented the fabrication of pure waxy rice starch nanofibers via electrospinning method and further revealed that the chemical structures of the material were not changed by this method. However, electrospun pure native starch materials always behaved with a relatively poor spinnability, weak mechanical properties, and low water stability.…”
Section: Electrospinning Natural Materialsmentioning
confidence: 99%
“…Besides the conventional spinning methods, different kinds of new spinning techniques have been developed and used for fiber spinning from starch and starch/polymer blends. Some of the novel developments in starch fiber production include electrospinning [ 19 , 37 , 38 , 39 , 40 ], electro wet-spinning [ 41 , 42 ], modified electro spinning [ 43 , 44 ] rotary or centrifugal spinning [ 45 , 46 , 47 ] and solution blowing [ 14 ]. From a feasibility point of view, conventional fiber production techniques are still more preferred, because they allow higher outputs and economic benefits [ 14 ].…”
Section: Possible Spinning Techniques For Starch Biopolymermentioning
confidence: 99%
“…In this research, water was used as the only solvent and polymeric dispersions were stirred at 80 °C for 15 min before electrospinning. From the result, it was revealed that unlike tapioca starch, the glutinous rice starch failed to generate nanofibers during the electrospinning [ 42 , 51 ].…”
Section: Possible Spinning Techniques For Starch Biopolymermentioning
confidence: 99%